The new essence of criminalistical activities as a variety of antidelictual activities - Ланцедова, Юлія Олександрівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2016)
In the article proposed a new understanding of the essence of the criminalistical activities as a kind of the antidelictual activities. Set out the roles of the antidelictual organs in the implementation of all stages of counter offenses and other related areas such opposition from state activities, that can be performed using the components of a vowel (criminalistical), so and the covert (ordystycal) methods in order to: 1) identify latent offenses; 2) termination of continuing violations; 3) disclosure violations; 4) pre-trial investigation or other pre clarify the circumstances of the offense; 5) judicial or extrajudicial final resolution of the case of a relevant offense; 6) pursuant to a final judicial or extra-judicial decisions; 7) of work with prisoners to withdrawal or redemption of conviction; 8) of the other preventive measures of offenses, primarily the causes and conditions that contributed to the commission of offenses, preparation of proposals of improvement of relevant laws and by-law of national regulation etc; 9) the implementation of appropriate generalizations antidelictual practice and identify its achievements and shortcomings; 10) the implementation of departmental and local sublegislative activities with the organization of this antidelictual organs and counter offense; 11) scientific research towards improving the efficiency, rationality and quality of criminalistical activities of the relevant species; 12) by means of higher educational institutions of the Ministry of Education training and skills development of criminalistical activities of the relevant type and self realization of current professional development. Outlined the essence of branches of the state power as legislative, enforcement and of the state power branch and special status of the court as the state power and as the branches of the state power. Formulated the concept antidelictual (criminalistical, ordystycal) activities as this type of state activity, the main purpose of which is the most effective, efficient and high-quality as combating different types of violations at each of the stages of vowel and covert implementation and functioning as the antidelictual organs, as well as to this end, the development of departmental and local by-law legal regulation of the relevant case summaries, research, training and retraining in educational institutions of the Ministry of Education and independent antidelictologeres current training of this kind of training.